2014
DOI: 10.1002/nmi2.46
|View full text |Cite
|
Sign up to set email alerts
|

Multi-drug resistance and reduced susceptibility to ciprofloxacin among Salmonella enterica serovar Typhi isolates from the Middle East and Central Asia

Abstract: Typhoid fever is common in developing countries, with an estimated 120 million infections and 700 000 annual deaths, worldwide. Fluoroquinolones have been the treatment of choice for infection with multidrug-resistant (MDR) Salmonella enterica serovar Typhi (S. Typhi). However, alarming reports of fluoroquinolone-resistance and failure of typhoid fever treatment have recently been published. To determine the proportion of S. Typhi isolates with reduced susceptibility to ciprofloxacin (RSC) from six countries i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
50
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 17 publications
12
50
0
1
Order By: Relevance
“…Diverse resistance patterns of various Salmonella strains to different antibiotics were found in our clinical study, which may be due to the different medical treatment expertise of doctors [17,20]. Nagshetty et al [17] reported that the percentage of Salmonella Typhi isolates resistant to ciprofloxacin in India was 4.2%, while the susceptibility of Salmonella to ciprofloxacin in the present study was 79.7%.…”
Section: Discussionmentioning
confidence: 73%
“…Diverse resistance patterns of various Salmonella strains to different antibiotics were found in our clinical study, which may be due to the different medical treatment expertise of doctors [17,20]. Nagshetty et al [17] reported that the percentage of Salmonella Typhi isolates resistant to ciprofloxacin in India was 4.2%, while the susceptibility of Salmonella to ciprofloxacin in the present study was 79.7%.…”
Section: Discussionmentioning
confidence: 73%
“…The use of antibiotics prior to blood collection may possibly explain the low isolation rate of Salmonella in Nepal, since antibiotics are frequently prescribed even for mild cases of fever. 9,10 The numbers of S. Paratyphi (41.18 %) were comparatively higher than S. Typhi. Increasing prevalence of S. Paratyphi has been reported from several studies worldwide including Nepal.…”
Section: Discussionmentioning
confidence: 96%
“…High incidence of NARS isolates, ranging from 73.3 to 94.9%, was described from different studies held in Nepal. 4,10,13 Nalidixic acid screening has been suggested to detect and predict decreased ciprofloxacin susceptibility in enteric fever causing Salmonella. 14,15 In our study, all 34 NARS isolates were found to be sensitive to ciprofloxacin by routine disc diffusion tests.…”
Section: Discussionmentioning
confidence: 99%
“…Before antibiotics were available, in one hospital in Indonesia 26% of patients hospitalized with blood culture confirmed Salmonella Typhi died [1]. Although most patients infected with strains of Salmonella Typhi and Salmonella Paratyphi A, B and C respond well to currently available antibiotics, the emergence of widespread antimicrobial resistance has undermined the effectiveness of commonly used antimicrobials [2][3][4]. There is little short term prospect for development of new effective low-cost drugs [5,6].…”
Section: Importance Of Enteric Fever Surveillancementioning
confidence: 99%